Evaluation of Polymer Concentration Effect on Doxycycline Hyclate Drug Release from in SituForming System based on Poly(lactide-co-glycolide) - H. Farrokhzad; H. Mobedi; J. Barzin; A. Poorkhalil (علوم و تکنولوژی پلیمر, 2009)
In this study, doxycycline hyclate release behavior from in situ forming drug delivery systems investigated. These systems based on poly()lactide-co-glycolide)(50:50 dissolved in N-methyl-2-pyrrolidone that were evaluated in different concentrations. These systems are useful for local treatment of periodontal diseases. UV spectroscopy is used to determine drug concentration in release medium. Also, a new method to stabilize drug in release medium was developed. The structure of prepared membranes is explained by scanning electron microscopy ()SEM) to evaluate the surficial and cross-sectional structures of polymer matrices. With increasing in polymer concentration, surface porosity decreased, membrane structure became denser, burst decreased and drug release time increased.